2001
DOI: 10.1128/jcm.39.11.3969-3975.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Rotaviruses in Nigeria: Detection of Unusual Strains with G2P[6] and G8P[1] Specificities

Abstract: During an epidemiological study on rotaviruses among diarrheic children in the northeastern and middle belt regions of Nigeria, the distribution of G and P types was investigated in 127 stool specimens. By PCR G typing, the G type of rotaviruses in 97 samples was identified. Interestingly, an unusual G8 type, as well as common G1, G2, and G3 types, was detected more frequently (31 of 112; 27.7%). Eleven samples contained multiple G types, and a G9 strain (Bulumkutu) was identified for one of the probable mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
3
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 35 publications
(55 reference statements)
10
106
3
1
Order By: Relevance
“…Furthermore, we documented the first case of G1/G8 mixed infection in Iran. Also, the first reports of G1/G8 mixed infection have been documented in young children with gastroenteritis in Ireland and Nigeria [29,30]. We found mixed infections with two different rotavirus genotypes in 2.66 % of children, which is similar to previous studies, with a range of 1-26.4 % [31].…”
Section: Rotavirus Genotypingsupporting
confidence: 90%
“…Furthermore, we documented the first case of G1/G8 mixed infection in Iran. Also, the first reports of G1/G8 mixed infection have been documented in young children with gastroenteritis in Ireland and Nigeria [29,30]. We found mixed infections with two different rotavirus genotypes in 2.66 % of children, which is similar to previous studies, with a range of 1-26.4 % [31].…”
Section: Rotavirus Genotypingsupporting
confidence: 90%
“…The detection of G1 serotypes as the most common strain is not surprising as it is the most abundant rotavirus strain globally. 8,35,37,38 Rotavirus with VP4 P [6] genotype was the only genotype detected in this study. The P [6] genotype was previously thought to be associated with neonatal rotavirus strains and hence thought to be associated with asymptomatic infection.…”
Section: Discussionmentioning
confidence: 85%
“…1) associated with diarrhea in children in Burkina Faso. Adah et al [2001] and Salu et al [2003] reported about a decade ago the existence of this genotypes in the region. Recently, the importance of G2P [6] in Burkina Faso has been reported .…”
Section: Discussionmentioning
confidence: 99%